Extracorporeal Life Support as a Bridge to Surgery of Acute Ventricular Septal Defect - Tulun, Aysun; Panholzer, Bernd; Cremer, Joachim; Haneya, Assad (The Thoracic and Cardiovascular Surgeon Reports, 2020)
Background Postinfarction ventricular septal defect (VSD) is a rare but life-threatening complication of acute myocardial infarction (AMI). Surgery represents the treatment of choice. But the optimal timing for surgery is still under debate.Case Description Here, we present the case of a 70-year-old female patient with an anterior postinfarction VSD leading to cardiogenic shock for whom we used a percutaneous implantation of an extracorporeal life support (ECLS) as a bridge to surgery. After 10 days of ECLS therapy, surgical VSD repair was successfully performed.Conclusion The strategy of delayed surgery may be a reasonable solution in selected patients with VSD complicating AMI.
Keywords: myocardial infarction; extracorporeal life support oxygenation; ECLS